Structural Reliability of Jacket Platforms using Second Order Reliability Method - Wan, Yin Huan (2015)
Jacket platform is the base structure for offshore oil processing topside structure which is used for continuous processing of crude oil. However, jacket platforms are subject to very harsh environments, subjected to extreme and operational conditions. Seawater comprises of salty and oxygenated water with high pH level that accelerates the process of corrosion and constant wave and current striking the jacket causes fatigue. This decreases the reliability index of the structure and increases the probability of failure of the structure at the same time. Due to the importance of the safety of structures, methods for the reliability assessment such as First-order Reliability Method (FORM), Second-order Reliability Method (SORM) and Monte Carlo Simulation (MCS) have been developed. This research will check the reliability of jacket elements under isolated and combined stresses by using Second Order Reliability Method which has not been used in previous studies.